Recurrent Painful Ophthalmoplegic Neuropathy and Oculomotor Nerve Schwannoma: A Pediatric Case Report with Long-Term MRI Follow-Up and Literature Review - Maria Giuseppina Petruzzelli; Mariella Margari; Flora Furente; Maria Carmela Costanza; Anna Rosi Legrottaglie; Franca Dicuonzo; Lucia Margari (Pain Research and Management)
Background. Recurrent painful ophthalmoplegic neuropathy (RPON), previously known as ophthalmoplegic migraine (OM), is an uncommon disorder with repeated episodes of ocular cranial nerve neuropathy associated with ipsilateral headache. The age of presentation is most often during childhood or adolescence. MRI has a central role in the assessment of the RPON, especially to distinguish orbital, parasellar, or posterior fossa lesions that mimic symptoms of RPON. Actually, oculomotor nerve tumors may be masquerade as RPON so that MRI follow-ups are required to detect the possibility of tumor etiology. Case presentation. We report a 16-year-old boy with a 7-year follow-up and multiple brain MRI data, previously diagnosed as OM. The last brain MRI, performed during an acute phase of oculomotor paresis with ipsilateral headache, showed a nodular lesion described as schwannoma of III cranial nerve. Then, we reviewed the literature on OM and RPON in pediatric age with a focus on brain MRI findings. Conclusions. This review highlights the important role of serial brain MRIs in the long-term follow-up of RPON, especially in the cases with childhood onset, in order to not delay the diagnosis of a possible oculomotor nerve schwannoma.